1989
DOI: 10.1007/978-3-642-74529-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Microspheres: Vaccine Delivery System for Oral Immunization

Abstract: The potential of biocompatible and biodegradable microspheres as a controlled release oral vaccine delivery system has been examined. Orally-administered 1-10 11m microspheres composed of poly (DL-Iactide-co-glycolide) were specifically taken up into the Peyer's patch lymphoid tissue of the gut, where those ~ 5 !lID remained for up to 35 days. Microspheres < 5 11m disseminated within macrophages to the mesenteric lymph nodes and spleen. In contrast to soluble staphylococcal enterotoxin B toxoid, oral immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…over negative control was significant (Figure 1 In living tissue, filaments composed of lactide-50 coglycolide copolymers are non-antigenic, non-pyrogenic, non-toxic' 9 , and degrade over time at rates largely determined by the molar ratios of the lactide to glycolide" . The inertness and orderly degradation of Elo-dge et al 4 reported markedly increased antianimals I week after vaccination (Figure 4). In both the enterotoxin IgA titres in gut fluids of mice orogastrically AF/RI-MS vaccinated and unvaccinated groups, a given microspheres incorporating staphylococcal enterovigorous antibody response, to about the same level, toxin B compared with titres in mice given soluble toxin.…”
Section: ?mentioning
confidence: 92%
“…over negative control was significant (Figure 1 In living tissue, filaments composed of lactide-50 coglycolide copolymers are non-antigenic, non-pyrogenic, non-toxic' 9 , and degrade over time at rates largely determined by the molar ratios of the lactide to glycolide" . The inertness and orderly degradation of Elo-dge et al 4 reported markedly increased antianimals I week after vaccination (Figure 4). In both the enterotoxin IgA titres in gut fluids of mice orogastrically AF/RI-MS vaccinated and unvaccinated groups, a given microspheres incorporating staphylococcal enterovigorous antibody response, to about the same level, toxin B compared with titres in mice given soluble toxin.…”
Section: ?mentioning
confidence: 92%
“…In relation to oral immunization, Peyer's patch M cells were reported to be able to transport biodegradable microspheres less then 5 μm in diameter [37]. Therefore, the development of efficient needle-free, oral vaccine delivery systems-a hope long held by all involved with immunization-needs to consider the particle-transporting capability of the M cell.…”
Section: Oral and Transcutaneous Vaccine Delivery Systemsmentioning
confidence: 99%
“…We, and others, have shown that the systemic injection of staphylococcal enterotoxin B toxoid (14)(15)(16)(21)(22)(23), influenza vaccine (24), simian immunodeficiency virus (SIV) vaccine (22) or ovalbumin (25,26) encapsulated in 1-10 pxn DL-PLG microspheres results in a strongly potentiated antibody response. In the case of SEB toxoid, mice immunized with 50 gtg of vaccine in microspheres mounted a neutralizing plasma anti-toxin response which was equivalent in level and duration to that induced by the same dose of toxoid in complete Freund's adjuvant (CFA), but without an inflammatory response (14).…”
Section: Introductionmentioning
confidence: 99%
“…DL-PLG microspheres have also been found to be an effective vehicle for mucosal immunization via the oral (15,16,21,23) and intratracheal (22,23) routes. This activity is attributable to the protection against nonspecific and specific proteolytic degradation provided by the encapsulation, as well as the enhanced and targeted delivery of the intact vaccine into the MALT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation